2014
DOI: 10.1186/1752-1947-8-470
|View full text |Cite
|
Sign up to set email alerts
|

Bowel obstruction caused by an internal hernia that developed after laparoscopic subtotal colectomy: a case report

Abstract: IntroductionLaparoscopic surgery is a minimally invasive approach with good treatment outcomes and is currently the standard surgery for colorectal cancer in Japan. Mesenteric closure is considered unnecessary in laparoscopic colorectal surgery because it can damage the bowel and blood vessels. However, an internal hernia may develop if the mesentery is not repaired.Case presentationWe report a case of internal hernia in a 61-year-old male of Japanese ethnicity. The patient had advanced sigmoid colon cancer, e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 13 publications
0
10
0
Order By: Relevance
“…At re‐operation, the mesenteric defect was closed in 52.2% (12/23; 8 ns) of cases. Six mesenteric defects were closed with suture and six with fibrin glue to approximate the mesentery of the neo‐colon to the posterior peritoneum. While nonabsorbable sutures were recommended in several studies , only one study specified the type of suture used and this was an absorbable 3‐0 vicryl.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…At re‐operation, the mesenteric defect was closed in 52.2% (12/23; 8 ns) of cases. Six mesenteric defects were closed with suture and six with fibrin glue to approximate the mesentery of the neo‐colon to the posterior peritoneum. While nonabsorbable sutures were recommended in several studies , only one study specified the type of suture used and this was an absorbable 3‐0 vicryl.…”
Section: Resultsmentioning
confidence: 99%
“…In four studies, the method of mesenteric defect closure at re-operation was continuous suturing [7][8][9][10]. In one study, fibrin glue was used in six cases [11].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, some authors reported SBO due to IH after laparoscopic colorectal surgery (LCRS) (2)(3)(4)(5)(6). This rising trend can be seen because laparoscopic colorectal surgery is now performed commonly worldwide.…”
Section: Introductionmentioning
confidence: 99%
“…22 However, it should be noted that, even taking this precaution, there are some cases of intestinal obstruction due to IH, similarly to occurred with the patient of the present report. 25,26 The precise diagnosis that an intestinal obstruction results from the development of an IH, begins with a careful clinical history. Importantly, the time to onset of symptoms between the initial surgery and the bowel obstruction may vary from hours to years.…”
Section: Discussionmentioning
confidence: 99%